The effects of majority versus minority source status on persuasion a self-validation analysis .[article]. - Horcajo, Javier
The present research proposes that sources in the numerical majority Vs,. minority) can affect persuasion by influencing the confidence with which people hold their thoughts in response to the persuasive message. Participants received a persuasive message composed of either strong or weak arguments that was presented by a majority or a minority source. Consistent with the self-validation hypothesis, we predicted and found that the majority (vs. minority) status of the source increased the confidence with which recipients held their thoughts. As a consequence, majority(vs. minority) sources increase argument quality effects in persuasion when source status information followed message processing(Experiment 1). In contrast, when the information regarding source status preceded (rather than followed) the persuasive message, it validated the perception of the position advocate, reducing message processing. As a consequence of having more confidence in the position advocated before receiving the message, majority(vs. minority) sources reduced argument quality effects on persuasion (Experiment 2). Finally, Experiment 3 isolated the timing of the source status manipulation, revealing that sources in the numerical majority (vs. minority) can increase or decrease persuasion to strong arguments depending on whether source status in introduced before or after processing the message.
Keywords: Attitudes; Persuasion; Minority status; Validation; Metacognition